Analisis Efektivitas dan Efisiensi Realisasi Anggaran Pendapatan dan Belanja Daerah Kota Jambi Tahun 2019-2024 - Azzahara, Salsa Devina; Hodijah , Siti (Jurusan Akuntansi FEB Universitas Jambi, 2026)
This study analyzes the growth, effectiveness, and efficiency of the Jambi City Regional Revenue and Expenditure Budget (APBD) during the 2019-2024 period as an indicator of good financial governance. The study employs a quantitative descriptive method using secondary data from the Budget Realization Reports (LRA) of the Jambi City Government from 2019 to 2024. The analysis measures APBD growth through growth ratios, effectiveness through effectiveness ratios, and efficiency through efficiency ratios. The results indicate that regional revenue and expenditure realization fluctuated but generally showed an increasing trend over the study period. The Jambi City Government effectively achieved its revenue targets with effectiveness ratios ranging from 93.6% to 101.4%, although it still needs to optimize expenditure management to improve budget efficiency, as reflected by efficiency ratios ranging from 88.7% to 93.3%.